A multiple intelligences theory-based 3D virtual lab environment for digital systems teaching. - Amorim, Toni [UNESP]; Tapparo, Leandro; Marranghello, Norian; Silva, Alexandre C. R. [UNESP]; Pereira, Aledir S. (Elsevier B.V., 2014)
This paper describes a 3D virtual lab environment that was developed using OpenSim software integrated into Moodle. Virtuald software tool was used to provide pedagogical support to the lab by enabling to create online texts and delivering them to the students. The courses taught in this virtual lab are methodologically in conformity to theory of multiple intelligences. Some results are presented.
Keywords: 3D Virtual Environments; Learning Management Systems; OpenSim; Sloodle